2007
DOI: 10.1097/01.phh.0000267688.54024.09
|View full text |Cite
|
Sign up to set email alerts
|

The 2005 British Columbia Smoking Cessation Mass Media Campaign and Short-term Changes in Smoking

Abstract: The overall poorer performance of high-risk groups is attributed to high exposure to cigarette smoking, which reduces a smoker's chances of successful cessation. In particular, high-risk groups are by definition more likely to be exposed to smoking by peers, but are also less likely to work in workplaces with smoking bans, which are shown to have a substantial impact on prevalence. Results suggest that for mass media campaigns to be more effective with high-risk groups, they need to be combined with other ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Most of the evidence in favour of the effectiveness of mass media campaigns (MMCs) in reducing adult smoking prevalence and cigarette consumption comes from studies evaluating campaigns run for short time‐periods in countries with little other tobacco control (TC) activity. These studies, conducted in the mid‐1970s to mid‐1990s , were either community‐level studies with intervention and control communities or population‐level studies , with most focusing on television campaigns , generally considered the most powerful medium to appeal to mass audiences. Since the 2000s, many countries began to run large‐scale MMCs for extended periods of time as part of multi‐component national TC programmes, rendering the findings from these earlier studies of limited relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the evidence in favour of the effectiveness of mass media campaigns (MMCs) in reducing adult smoking prevalence and cigarette consumption comes from studies evaluating campaigns run for short time‐periods in countries with little other tobacco control (TC) activity. These studies, conducted in the mid‐1970s to mid‐1990s , were either community‐level studies with intervention and control communities or population‐level studies , with most focusing on television campaigns , generally considered the most powerful medium to appeal to mass audiences. Since the 2000s, many countries began to run large‐scale MMCs for extended periods of time as part of multi‐component national TC programmes, rendering the findings from these earlier studies of limited relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the impacts of tobacco price and taxation, smoking cessation mass media campaigns, and sales restrictions differ by gender, education level, occupational status, and smoking status [3-5]. It has been proposed that these various responses to tobacco policy are due to a lack of consideration of the social context [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that these various responses to tobacco policy are due to a lack of consideration of the social context [3]. Therefore, previous studies have suggested that in order to strengthen and improve the effect of tobacco policies, it is necessary to develop a comprehensive understanding of smoking behavior by considering the social context [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study is to evaluate the impact of the campaign on the panel's attitudes towards smoking. A related study looked at the impact of the campaign on short-term prevalence and quantities smoked using the Canadian Tobacco Use Monitoring Survey with a quasi-experimental approach and found statistically significant differences that could be attributed to the campaign (Gagné, 2007).…”
mentioning
confidence: 98%